2022
DOI: 10.1007/s12672-022-00546-6
|View full text |Cite
|
Sign up to set email alerts
|

Metadata analysis to explore hub of the hub-genes highlighting their functions, pathways and regulators for cervical cancer diagnosis and therapies

Abstract: Cervical cancer (CC) is considered as the fourth most common women cancer globally.that shows malignant features of local infiltration and invasion into adjacent organs and tissues. There are several individual studies in the literature that explored CC-causing hub-genes (HubGs), however, we observed that their results are not so consistent. Therefore, the main objective of this study was to explore hub of the HubGs (hHubGs) that might be more representative CC-causing HubGs compare to the single study based H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 144 publications
0
0
0
Order By: Relevance
“…By disrupting cell cycle progression and inducing DNA damage, TYMS may lead to changes in PLK1 expression and activity, affecting processes such as proliferation, apoptosis, and EMT in tumor cells. Previous studies have suggested that TYMS and PLK1 may serve as prognostic markers for certain tumors 49,50 , but little is known about their speci c roles and mechanisms of interaction. Therefore, our study is the rst to provide evidence of TYMS's direct positive regulatory effect on PLK1 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…By disrupting cell cycle progression and inducing DNA damage, TYMS may lead to changes in PLK1 expression and activity, affecting processes such as proliferation, apoptosis, and EMT in tumor cells. Previous studies have suggested that TYMS and PLK1 may serve as prognostic markers for certain tumors 49,50 , but little is known about their speci c roles and mechanisms of interaction. Therefore, our study is the rst to provide evidence of TYMS's direct positive regulatory effect on PLK1 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to collect useful and important data related to the study before using any technique. This process of collection of data is called data mining [18]. Oncomine is the name of the software system utilized in the data mining procedure.…”
Section: Bioinformatics Databases and Toolsmentioning
confidence: 99%